Pengaruh Pemberlakukan Pembatasan Sosial Berskala Besar (PSBB) Terhadap Pertumbuhan Ekonomi di Kota Bandar Lampung Saat Pandemi Covid-19 Perspektif Ekonomi Islam - muhammad suhaidi; Ade Eko Setiawan; Miswan Gumanti; Sudewi Sudewi; Wulandari Wulandari (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the enforcement effect of PSBB on economic growth in Bandar Lampung City during covid-19 pandemic and determine the enforcement effect of PSBB on economic growth in Bandar Lampung City during covid-19 pandemic in perspective Islamic Economics. This study use quantitative method. The data analysis technique used is a simple regresstion analysis. The type of data used is primary data. In this study there is one independent variabel and one dependent variabel, the independent variabel in this study is the influence of PSBB and the dependent variabel in this study is economic growth. The type of data used is interval data with a likert scale. In this study, method of collecting data used is an online quetionnaires, use the google form facility to distribute quetionnaires. Overall research results showed that the PSBB has no a positive effect and significant on economic growth in Bandar Lampung City during covid-19 pandemic and in an Islamic economics perspective, the PSBB has no a positive effect and significant on economic growth in Bandar Lampung City during covid-19 pandemic. Because in Islam to increase economic growth emphasizes more equal distribution. With existing research results, it can be concluded that the distribution continues to run well even in a pandemic state.